Epidemiological survey of echinococcosis in Tibet Autonomous Region of China - Bin Li; Gongsang Quzhen; Chui-Zhao Xue; Shuai Han; Wei-Qi Chen; Xin-Liu Yan; Zhong-Jie Li; M. Linda Quick; Yong Huang; Ning Xiao; Ying Wang; Li-Ying Wang; et al. (BMC, 2019)
Abstract Background The echinococcosis is prevalent in 10 provinces /autonomous region in western and northern China. Epidemiological survey of echinococcosis in China in 2012 showed the average prevalence of four counties in Tibet Autonomous Region (TAR) is 4.23%, much higher than the average prevalence in China (0.24%). It is important to understand the transmission risks and the prevalence of echinococcosis in human and animals in TAR. Methods A stratified and proportionate sampling method was used to select samples in TAR. The selected residents were examined by B-ultrasonography diagnostic, and the faeces of dogs were tested for the canine coproantigen against Echinococcus spp. using enzyme-linked immunosorbent assay. The internal organs of slaughtered domestic animals were examined by visual examination and palpation. The awareness of the prevention and control of echinococcosis among of residents and students was investigated using questionnaire. All data were inputted using double entry in the Epi Info database, with error correction by double-entry comparison, the statistical analysis of all data was processed using SPSS 21.0, and the map was mapped using ArcGIS 10.1, the data was tested by Chi-square test and Cochran-Armitage trend test. Results A total of 80 384 people, 7564 faeces of dogs, and 2103 internal organs of slaughtered domestic animals were examined. The prevalence of echinococcosis in humans in TAR was 1.66%, the positive rate in females (1.92%) was significantly higher than that in males (1.41%), (χ 2 = 30.31, P < 0.01), the positive rate of echinococcosis was positively associated with age (χ 2 trend = 423.95, P < 0.01), and the occupational populations with high positive rates of echinococcosis were herdsmen (3.66%) and monks (3.48%). The average positive rate of Echinococcus coproantigen in TAR was 7.30%. The positive rate of echinococcosis in livestock for the whole region was 11.84%. The average awareness rate of echinococcosis across the region was 33.39%. Conclusions A high prevalence of echinococcosis is found across the TAR, representing a very serious concern to human health. Efforts should be made to develop an action plan for echinococcosis prevention and control as soon as possible, so as to control the endemic of echinococcosis and reduce the medical burden on the population.